2008
DOI: 10.1177/0731684407079777
|View full text |Cite
|
Sign up to set email alerts
|

Application of Folded Plate Formulation in Analyzing Stiffened Laminated Composite and Sandwich Folded Plate Vibration

Abstract: A nine noded flat plate element, considering first order transverse shear deformation and rotary inertia with five degrees of freedom per node, is used to compute element stiffness and mass matrices for composite plates. Drilling degrees of freedom are introduced to account for three translations and three rotations per node, and transformed to obtain the global matrices for computing the dynamic response of stiffened laminated composite and sandwich folded plate structures. The stiffeners are visualized as pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 11 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…In addition, basing on the first order shear deformation theory (FSDT), Niyogi et al [12] used a nine-node plate bending element with an additional drilling DOF to analyze the free and forced vibration responses of composite folded plate structures. The method was then extended for frequency optimization problem by Topal and Uzman [25], and for dynamic analysis of stiffened ones by Pal and Niyogi [23]. In spite of being popular in dealing with diverse solid mechanic problems, few finite element schemes using triangular elements have been developed and applied to folded plates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, basing on the first order shear deformation theory (FSDT), Niyogi et al [12] used a nine-node plate bending element with an additional drilling DOF to analyze the free and forced vibration responses of composite folded plate structures. The method was then extended for frequency optimization problem by Topal and Uzman [25], and for dynamic analysis of stiffened ones by Pal and Niyogi [23]. In spite of being popular in dealing with diverse solid mechanic problems, few finite element schemes using triangular elements have been developed and applied to folded plates.…”
Section: Introductionmentioning
confidence: 99%
“…Some highlighted numerical methods that have been proposed to analyze folded plate structures are the finite strip element methods [13][14][15][16], the combined boundary elementtransfer matrix method [17], the finite element method (FEM) [3,12,[18][19][20][21][22][23][24][25][26][27][28], the mesh-free Galerkin method [2,29]. Among these methods, the FEM, which is highly appreciated by the effectiveness and the extensibility for various problems, has taken much attention from researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Table 4. E-glass Epoxy material properties [10] and presented in Table 5. It is shown that the five natural frequencies …”
Section: Validation Examplementioning
confidence: 99%
“…In the example, the first five natural frequencies of a cantilever two folded composite plate studied by Guha Niyogi [10] are recalculated. The authors of [10] used 72 nine nodes elements for modeling.…”
Section: Validation Examplementioning
confidence: 99%
See 1 more Smart Citation